2008
DOI: 10.1073/pnas.0800005105
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for the right fronto-insular cortex in switching between central-executive and default-mode networks

Abstract: Cognitively demanding tasks that evoke activation in the brain's central-executive network (CEN) have been consistently shown to evoke decreased activation (deactivation) in the default-mode network (DMN). The neural mechanisms underlying this switch between activation and deactivation of large-scale brain networks remain completely unknown. Here, we use functional magnetic resonance imaging (fMRI) to investigate the mechanisms underlying switching of brain networks in three different experiments. We first exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

213
2,236
2
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,494 publications
(2,515 citation statements)
references
References 53 publications
213
2,236
2
10
Order By: Relevance
“…However, more recent models have introduced the crucial role of the SN to control the state-dependent switching between DMN and task-related attention networks [15]. Specifically, studies found support for a central role of the SN in attenuating the DMN and upregulating attention networks when switching from rest-to-task [19,20]. Interestingly, our results imply an intact between DMN and SN connectivity in ADHD, and indicate another locus of functional disorganisation that may relate to attention deficits, namely, the imbalance between SN and attention networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent models have introduced the crucial role of the SN to control the state-dependent switching between DMN and task-related attention networks [15]. Specifically, studies found support for a central role of the SN in attenuating the DMN and upregulating attention networks when switching from rest-to-task [19,20]. Interestingly, our results imply an intact between DMN and SN connectivity in ADHD, and indicate another locus of functional disorganisation that may relate to attention deficits, namely, the imbalance between SN and attention networks.…”
Section: Discussionmentioning
confidence: 99%
“…Support for this view comes from a range of recent studies [16][17][18][19][20]. 4 Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental condition characterised in part by symptoms of distractibility and an inability to ignore irrelevant stimuli -characteristics related to deficits in attentional control [21].…”
Section: Introductionmentioning
confidence: 99%
“…They found that gaze shifts increased the connectivity of right pSTS with the dorsal attention network including the right intraparietal sulcus (IPS) and right frontal eye field (FEF). The dorsal attention network is thought to control endogenous attention mechanisms to enhance sensory processing of task-relevant stimuli, whereas a more ventral attention system within the fronto-insular cortex comprising the anterior insula (aIns) and neighboring inferior frontal gyrus (IFG) may act as circuit-breaker that switch processing resources from the default mode network to the central-executive (Sridharan et al, 2008) and reorient attention toward unexpected but behaviorally significant stimuli (Corbetta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The DMN was initially considered to represent neural baseline activity until further investigations showed that activity within the DMN is functionally related to internally driven mental states, such as self-referential processing, long-term memory, and mentalizing, and that its deactivation plays a functional role during externally directed tasks (Anticevic et al, 2012;Buckner et al, 2008;Burianova, McIntosh, & Grady, 2010;Kelly et al, 2008;Mennes et al, 2010;Sambataro et al, 2010). In addition, an emerging view suggests that cognitive performance in general might rely on the dynamic interaction between the DMN and two other large-scale neural networks: the fronto-parietal task-positive network (FPN), which is associated with attention and cognitive control, and the salience network (SN) in anterior cingulate and fronto-insular cortex, which is involved in the selection of emotionally and motivationally relevant stimuli (Andrews-Hanna et al, 2014;Chen et al, 2013;Fox et al, 2005;Seeley et al, 2007;Sridharan et al, 2008;Spreng et al, 2013). These three neural networks are central to cognition, as they are engaged in a large number of functions, and their disruption has been associated with a variety of clinical syndromes, such as schizophrenia, traumatic brain injury, and Alzheimer's disease (Manoliu et al, 2014;Sharp et al, 2014;Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%